Performance Audit on Private Universities and Private Colleges in Punjab (2010-2015) - CAG of India (CAG of India)
With a view to develop and implement a fair and transparent framework that provides sufficient opportunities to the deserving private institutes and educational promoters for higher education, Government of Punjab notified (June 2010) ‘The Punjab Private Universities Policy, 2010’ for establishment of Private Universities (PUs). Private Colleges (PCs) of the Punjab State are to be affiliated with Government Universities only. Some of the significant findings of the Performance Audit are given below: 1. No regulatory mechanism for private universities was set up at State Government level to safeguard the interests of stakeholders. (Paragraph 2.1.6.1) 2. Deficiencies were noticed in the process of establishment of seven Private Universities (PUs) in violation of Punjab Private University Policy, 2010. (Paragraph 2.1.6.2) 3.Five PUs and 12 PCs were established without obtaining the permission for change of land use and seven PUs and six PCs were approved without the approval of building plans leading to non-recovery of external development charges and licence fee and thus extending undue financial favour of ₹ 7.95 crore to promoters/sponsoring bodies. Further, there was loss to the Government due to non-recovery of labour cess of ₹ 1.48 crore in four cases where building plans were not approved. (Paragraph 2.1.6.3(ii & iii)) 4. Five PUs commenced academic operations without obtaining clearance from the University Grants Commission (UGC). (Paragraph 2.1.7.1) 5. Six PUs and 16 PCs had appointed 148 and 440 faculty members respectively without following eligibility criteria and State Universities were granting affiliation to the private colleges having inadequate infrastructure, facilities, etc. (Paragraphs 2.1.8.1 (i & ii) and 2.1.8.4) 6. No periodical inspection was conducted for any of the PUs by UGC. Punjab Technical University had conducted academic audit of 92 colleges out of 292 during 2010-14 whereas Punjabi University, Patiala had not conducted periodic inspection of any of 194 PCs affiliated with it. (Paragraphs 2.1.9.1 and 2.1.9.4(i&ii))
For the Period 2010-2015